Prospective Associations Between Maternal Depression and Infant Sleep in Women With Gestational Diabetes Mellitus - Gilbert, Leah; Sandoz, Vania; Quansah, Dan Yedu; Puder, Jardena J.; Horsch, Antje (Frontiers in Psychology, 2022)
Background Women with gestational diabetes mellitus have higher rates of perinatal depressive symptoms, compared to healthy pregnant women. In the general population, maternal depressive symptoms have been associated with infant sleep difficulties during the first year postpartum. However, there is lack of data on infants of mothers with gestational diabetes mellitus. Methods This study assessed the prospective associations between maternal perinatal depressive symptoms and infant sleep outcomes. The study population consisted of 95 Swiss women with gestational diabetes mellitus and their infants, enrolled in the control group of the MySweetheart trial (NCT02890693). Perinatal depressive symptoms were assessed with the Edinburgh Postnatal Depression Scale at the first gestational diabetes mellitus visit during pregnancy, at 6–8 weeks postpartum, and 1 year postpartum. The Brief Infant Sleep Questionnaire was used to assess infant sleep (i.e., nocturnal sleep duration, number of night waking, and maternal perception of infant sleep) at 1 year postpartum. Relevant maternal and infant measurements (e.g., infant sex or maternal age or social support) were collected or extracted from medical records as covariates. Results Antenatal maternal depressive symptoms at the first gestational diabetes mellitus visit were inversely associated with infant nocturnal sleep duration at 1 year postpartum (β = –5.9, p = 0.046). This association became marginally significant when covariates were added (β = –5.3, p = 0.057). Maternal depressive symptoms at 6–8 weeks postpartum were negatively and prospectively associated with infant nocturnal sleep duration (β = –9.35, p = 0.016), even when controlling for covariates (β = –7.32, p = 0.042). The association between maternal depressive symptoms and maternal perception of infant sleep as not a problem at all was significant at 1 year postpartum (β = –0.05, p = 0.006), although it became non-significant when controlling for appropriate covariates. No other significant associations were found. Limitations This study solely included measures derived from self-report validated questionnaires. Conclusion Our findings suggest it is of utmost importance to support women with gestational diabetes mellitus as a means to reduce the detrimental impact of maternal perinatal depressive symptoms on infant sleep, given its predictive role on infant metabolic health.